Identification of a prototype human gut Bifidobacterium longum subsp. longum strain based on comparative and functional genomic approaches - Alessandri, Giulia; Fontana, Federico; Tarracchini, Chiara; Rizzo, Sonia Mirjam; Bianchi, Massimiliano G.; Taurino, Giuseppe; Chiu, Martina; Lugli, Gabriele Andrea; Mancabelli, Leonardo; Argentini, Chiara; Longhi, Giulia; Anzalone, Rosaria; et al. (Frontiers in Microbiology, 2023)
Bifidobacteria are extensively exploited for the formulation of probiotic food supplements due to their claimed ability to exert health-beneficial effects upon their host. However, most commercialized probiotics are tested and selected for their safety features rather than for their effective abilities to interact with the host and/or other intestinal microbial players. In this study, we applied an ecological and phylogenomic-driven selection to identify novel B. longum subsp. longum strains with a presumed high fitness in the human gut. Such analyses allowed the identification of a prototype microorganism to investigate the genetic traits encompassed by the autochthonous bifidobacterial human gut communities. B. longum subsp. longum PRL2022 was selected due to its close genomic relationship with the calculated model representative of the adult human-gut associated B. longum subsp. longum taxon. The interactomic features of PRL2022 with the human host as well as with key representative intestinal microbial members were assayed using in vitro models, revealing how this bifidobacterial gut strain is able to establish extensive cross-talk with both the host and other microbial residents of the human intestine.